Compliance of the Physical Activity Guidelines Accumulated in Bouts >= 10 Min and Nonbouts and Its Association With Body Composition and Physical Function: A Cross-Sectional Study in Brazilian Older Adults - Silva Vilela Ribeiro, Anna Gabriela (2021)
This study aimed to investigate the association between compliance with the guidelines of moderate to vigorous physical activity (MVPA) accumulated in bouts of >= 10 min or nonbouts with body composition and physical function in older adults. The authors evaluated 230 noninstitutionalized older adults. Body composition was estimated using bioimpedance, and physical function was assessed using four physical tests. Physical activities were monitored for 7 days using an accelerometer. Older adults who were physically active according to MVPA in bouts of >= 10 min were less likely to have low appendicular skeletal muscle mass (odds ratio [OR] = 0.12), excess body fat (OR = 0.30), and abdominal obesity (OR = 0.34) and more likely to have a higher physical function (OR = 5.78). No significant association was observed with MVPA nonbout. Our findings indicate that older adults who accumulate MVPA in bouts of >= 10 min have better parameters for body composition and physical function.